(untitled) (Eurasian Medical Research Periodical, 2022)
In the modern world, the role of the family, the role of the school in the formation of a healthy lifestyle for children, a comprehensively developed personality is increasing. It is known that a person spends most of his life in the family. Indeed, in childhood, a child’s lifestyle is formed under the influence of the lifestyle of his parents and friends.